The Impact of Herbal Drug Use on Adverse Drug Reaction Profiles of Patients on Antiretroviral Therapy in Zimbabwe - Tinashe Mudzviti; Charles C. Maponga; Star Khoza; Qing Ma; Gene D. Morse (AIDS Research and Treatment)
Background. The main objective was to determine the impact of herbal drug use on adverse drug reactions in patients on antiretroviral therapy (ART). Methodology. Patients receiving first-line ART from the national roll-out program participated in this cross-sectional study. Participants were interviewed and a data collection sheet was used to collect information from the corresponding medical record. Results. The majority (98.2%) of participants were using at least one herbal drug together with ART. The most common herbal remedies used were Allium Sativum (72.7%), Bidens pilosa (66.0%), Eucalyptus globulus (52.3%), Moringa oleifera (44.1%), Lippia javanica (36.3%), and Peltoforum africanum (34.3%). Two indigenous herbs, Musakavakadzi (OR=0.25; 95% CI 0.076–0.828) and Peltoforum africanum (OR=0.495; 95% CI 0.292–0.839) reduced the occurrence of adverse drug events. Conclusions. The use of herbal drugs is high in the HIV-infected population and there is need for pharmacovigilance programs to recognize the role they play in altering ADR profiles.